Resection of Calcified and Giant Thoracic Disc Herniation Through Bilateral Postero-Lateral Approach and 360° Cord Release: A Technical Note - Zaed, Ismail; Pommier, Benjamin; Capo, Gabriele; Barrey, Cédric Y. (Journal of clinical medicine, 2024)
Background/Objectives: Surgical treatment of thoracic disc herniation (TDH) is risky and technically demanding due to its proximity to the spinal cord and the high possibility of the TDH being calcified (up to 40%), making the resection even more complex. Calcified TDH may be resected from an anterior via thoracotomy/thoracoscopy, lateral extra-cavitary, or a postero-lateral approach. Here, we present our experience in managing such pathology with an original technique Methods: This original technique, used successfully in more than 40 patients, is introduced, with a precise description of the surgical anatomy and the surgical steps to take. Indications for surgical management and neurological outcomes are also analyzed. This surgical approach consisted of transverso-pediculectomy, most often bilaterally, partial vertebral body drilling, 360° release of the cord, and short fixation. Results: A total of 44 patients were collected, with a mean age of 52.4 ± 11.7 years. Seven patients (15.9%) had complete calcifications, and thirty-one had partial calcifications (70.5%), while the remaining six did not have signs of calcifications. There were only 4 intraoperative complications (2 dural tears and 2 loss of evoked potentials). The TDH could be resected in total for 39 patients (88.6%) and partially, according to the “floating” technique, in 5 patients (11.4%). In the postoperative follow-up, all of the patients except two (presenting with sensory aggravation) reported an improvement in neurological conditions leading to an overall risk of neurological aggravation of 4.5%. Conclusions: The bilateral postero-lateral approach provides a large decompression of the cord (360°) and gives safe access to the TDH, even calcified, permitting high rates of total resection. It also prevents any prejudicial pressure on the spinal cord, reducing the risk of severe postoperative deficits and permitting optimal instrumentation (pedicle screw-based) of the spinal segment. The surgical sequence to resect the bony structures around the spinal cord is of great importance.